Hydraulic fracturing: Assessing self-reported familiarity and the contributions of selected sources to self-reported knowledge. Issue 1 (January 2017) - Theodori, Gene L.; Ellis, Colter
Abstract: Data collected from a random sample of individuals in two counties in the Eagle Ford Shale region of South Texas to examine (a) respondents' self-reported familiarity with the process of hydraulic fracturing and (b) the associations between the contributions of information sources to self-reported knowledge about hydraulic fracturing and self-reported levels of familiarity with the process of hydraulic fracturing. The results of this study revealed that survey respondents in the Eagle Ford Shale region of Texas are more familiar with the process of hydraulic fracturing than has been reported in other studies. Moreover, the findings indicated that self-reported levels of familiarity with the process of hydraulic fracturing were positively associated with certain sources of information. Among those sources that reached statistical significance, the strongest contributor to respondents' self-reported familiarity with hydraulic fracturing was information from the oil/natural gas industry.